Monitoring symptoms at home: what methods would cancer patients be comfortable using? - Kleiboer A; Gowing K; Holm Hansen C; Hibberd C; Hodges L; Walker J; Thekkumpurath P; O'Connor M; Murray G; Sharpe M; Kleiboer, Annet; Gowing, Katie; et al. (Quality of Life Research, 2010)
Purpose: This study aimed to determine which methods of remote symptom assessment cancer outpatients would be comfortable using, including those involving information technology, and whether this varied with age and gender.Methods: A questionnaire survey of 477 outpatients attending the Edinburgh Cancer Centre in Edinburgh, UK.Results: Most patients reported that they would not feel comfortable using methods involving technology such as a secure website, email, mobile phone text message, or a computer voice on the telephone but that they would be more comfortable using more traditional methods such as a paper questionnaire, speaking to a nurse on the telephone, or giving information in person.Conclusions: The uptake of new, potentially cost-effective technology-based methods of monitoring patients' symptoms at home might be limited by patients' initial discomfort with the idea of using them. It will be important to develop methods of addressing this potential barrier (such as detailed explanation and supervised practice) if these methods are to be successfully implemented.